The Strategies of Conflict Management in the Managerial Organization (مجلة المنصور, 2022)
Conflict has widely captured the attention of researchers from all direction. Even though, the differences among these researchers are not essential. All focus on differences of interests and opinions among individuals, a difference that is usually found in people. The conflict has been examined from different points of view such as classical, behavioral and interactional. Each has its own administrative approach the researchers use different ways to manage and face conflict. Therefore,it becomes necessary for management of organization to use a way that copes with the level of conflict in the organization. This research paper falls into three parts. The first shows the concepts, stages and reasons of conflict. The management of conflict within the administration and organization the relevant approaches and the concerned previous studies. The results an recommendation that may be used by the administration and the organization to manage and control conflict are shown in the second part of this study.